Women’s Unpaid Work in the National Income : A Time Use-Data Analysis in India - S., Sreejith (Arthshastra Indian Journal of Economics & Research, 2025)
Purpose : This study used time-use data to examine women’s unpaid activities and their contribution to national income. It also compared the unpaid contributions of working and non-working women within and beyond SNA production boundaries. Methodology : The study used the cross-sectional time use dataset from the time use survey of India conducted in 2019. A sample of 329,680 individuals comprising 165,282 males and 164,398 females aged between 15 and 59 was selected from rural and urban areas. The cross-tabulation technique, percentage analysis, and Mann-Whitney U test were applied for data comparison and statistical analysis. Findings : The findings revealed that males performed more unpaid activities within the national income boundary than females in India. In contrast, women were more involved in unpaid activities outside the national income production boundary. Similarly, working women’s unpaid non-SNA work remains unchanged, though they were involved in paid activities in the labour market. Practical Implications : The study confirmed that the women’s contribution to unpaid work beyond the national income production boundary was immense, which remains unaccounted for in the formal national income estimation. These findings emphasized the need for targeted interventions and government policy reforms to address persistent gender disparity in unpaid work. Originality : This study conducted a segregated analysis of unpaid work that falls within and beyond the scope of national income estimation. Further, it explored the role of work status in women’s unpaid activities in India and provided evidence-based insights for policymakers.